Targeting Neuroinflammation and Neurodegeneration in Parkinson’s Disease - Oliveira, Sara (2022)
Parkinson’s disease (PD) is the second most common neurodegenerative disease worldwide, being mostly characterized by motor features correlating with dopaminergic neuronal degeneration in the substantia nigra pars compacta (SN) and striatum. Although predominantly sporadic, approximately 10% of all cases are classified as heritable forms of PD, with mutations in the leucine-rich repeat kinase 2 (LRRK2) gene being the most frequent known cause of familial PD. Necroptosis is a caspase-independent form of regulated cell death mediated by the strenuous action of receptor-interacting protein 3 (RIP3) and pseudokinase mixed lineage domain-like protein (MLKL), being also dependent on RIP1 kinase activity, according with the cellular context. Importantly, in the past few years, activation of necroptosis has been linked to PD, while necroptosis inhibition results in disease improvement, unveiling an alternative approach for therapeutic intervention. In turn, microRNAs (miRNAs or miRs), including miR-335, are small non-coding RNAs, whose deregulation has been associated with neurodegeneration and neuroinflammation in different neurodegenerative conditions, such as PD. Identification of deregulated miRNAs may serve as biomarkers for disease detection and prognosis prediction, can help in understanding the complex mechanism of neurodegenerative disease development, and their use in therapy may tackle several issues of aging and neurodegeneration. The main objectives of this thesis were to extend the current knowledge on therapeutic approaches in PD, mostly focusing on the discovery of novel small molecule inhibitors of necroptosis, as well as miRNAs that could represent promising therapeutic strategies and/or biomarkers of disease. In our first work, we phenotypically screened a library of 21 newly synthetized small compounds to identify novel inhibitors of necroptosis, using the BV2 murine microglial cell line treated with the well-known pan-caspase inhibitor, zVAD-fmk (zVAD). We identified one hit – compound Oxa12 – that strongly inhibited zVAD-induced necroptosis. Importantly, Oxa12 counteracted zVAD- and LPS-induced inflammation, by attenuating TNF-α and IL-1β expression. Moreover, Oxa12 negatively regulated JNK and p38 signalling pathways and NF-кB activation, thus suggesting an overall reduction of necroptosis-driven inflammation. In our second study, as a proof of concept, we evaluated the protective effect of Oxa12 in vivo, using the sub-acute 1-methyl-1-4-phenyl-1,2,3,6-tetrahydripyridine hydrochloride (MPTP) PD-related mouse model. Importantly, we observed that Oxa12 protected from MPTP-induced dopaminergic neuronal loss in the SN and striatum. A combination of the analysis of whether Oxa12 was included in the CNS drug property space, using a CNS-multiparameter optimization (MPO) score and metabolic data indicated that Oxa12 has a good brain exposure and an estimated half-life of 13 minutes, turning this compound into a novel addition to the chemical toolbox of CNS-targeting anti-necroptotic compounds. Overall, Oxa12 is a good drug candidate for further optimization to attenuate PD pathogenesis. Finally, we investigated the expression profile of a selected panel of miRNAs, previously linked to cell death and/or inflammatory pathways, in the serum of idiopathic PD (iPD) patients and patients carrying a mutation in the LRRK2 gene (LRRK2-PD), and aged-matched healthy controls, and investigated its value as molecular marker of disease pathogenesis. We determined a differential pattern of miRNA expression between PD patients and age- and gender-matched healthy individuals, with a downregulation of miR-146a, miR-335-3p and miR-335-5p in PD patients in comparison with controls, and no significant alteration in miR-21, miR-34a, miR-34c and miR-155. Interestingly, miR-155 was significantly upregulated in the serum of LRRK2-PD patients versus iPD patients. Since miR-146a role in neurodegenerative diseases with an inflammatory component was already better known, and in silico studies pointed LRRK2 as a putative target of miR-335, we decided to dissect the protective role of miR-335 in experimental models of PD, during inflammatory and/or neurodegenerative events. Our results clearly demonstrated that miR-335 is downregulated in various PD-mimicking conditions, including LPS-stimulated and/or LRRK2wt-overexpressing BV2 microglia cells. These results were further confirmed in the serum of MPTP-injected mice. In terms of mechanism, we confirmed that miR-335 directly targets LRRK2 mRNA. More importantly, miR-335 overexpression clearly counteracted proinflammatory gene expression induced by LPS and LRRK2wt, in BV2 and N9 microglia cells. Further, miR-335 also reduced LPS-induced RIP1 and RIP3 proteins and activation of ERK1/2 and NF-кB cascade. In SH-SY5Y neuroblastoma cells, miR-335 reduced α-synuclein-triggered proinflammatory gene expression. In conclusion, we identified one compound – Oxa12 – that strongly inhibits necroptosis in vitro, in the murine L929 fibroblast and BV2 microglia cell lines and protected from MPTP-driven dopaminergic neuronal loss in vivo, being therefore considered a strong drug candidate for further optimization to slow or attenuate PD pathogenesis. In addition, we identified different miRNA signatures between PD patients, including iPD and LRRK2-PD patients and healthy controls, and further unravelled novel roles for miR-335 in microglia and neuronal cells that halt chronic neuroinflammation effects induced by a classical inflammatory stimulus or even LRRK2wt overexpression. Overall, further characterization of the synergistic function of necroptosis inhibition and miRNA-based strategies may highlight their therapeutic potential for several neurodegenerative diseases with a strong neuroinflammatory component, such as PD.